MODIFICATION OF TENNIS BALLS ON SHOT PUT - Ahmad Lamusu (Jambura Journal of Sports Coaching, 2020)
This study aims to improve learning outcomes Reject Bullets through learning tools for modification of tennis balls for VII grade students of SMP Negeri I Telaga by using learning media for modifying tennis balls. This research is a classroom action research (CAR) consisting of two cycles and each cycle consists of three meetings. From the results of data analysis, the average student learning outcomes in how to hold a bullet, put a bullet and reject a bullet has increased. While 1 student did not reach the minimum completeness criteria set by the school, but it was already included in the sufficient criteria in Shot Put learning. This study proves that if a tennis ball modification is applied, the learning outcomes of Grade VII Bullet Resistant students of SMP Negeri I Telaga Gorontalo Regency have increased.